Uji Potensi Antibakteri Ekstrak Kulit Jeruk Nipis Citrus aurantifolia (Christm) Swingle Terhadap Vibrio sp. - Aziz Aziz; Evy Ratnasari Ekawati; Muhammad Sungging Pradana; Indra Adi Wira Prasetya; Nadiah Al Batati; Esti Rizkiana Pratiwi (Jurnal SainHealth, 2023)
Lime (Citrus aurantifolia) is one of the herbal plants that is rich in benefits, especially as a herbal medicines. Besides of lime fruit, lime peel also has antibacterial properties such as essential oils which contain flavonoids which can inhibit bacterial growth. This research utilizes lime peel which will be extracted as a test material. The purpose of this research is to determine the antibacterial potential of lime peel extract against Vibrio sp. at various concentrations. This research used the well-diffusion method using MHA as a test medium to determine whether lime peel extract can inhibit the growth of Vibrio sp. Various concentrations and penicillin as a positive control used in this research to determine which concentration has a greatest potential for inhibiting the growth of Vibrio sp. Result of this study used qualitative analysis by comparing the clear zone size produced on the medium. The obtained result shown that 20%, 40%, 60%, 80% and 100% concentration of lime peel can forming a clear zone which mean they can inhibit the growth ofÂ  Vibrio sp. The best concentration used to inhibit Vibrio sp. is 100% concentration which produce 23.7 mm clear zone on MHA medium. Lime peel extract can be used to inhibit Vibrio sp. growth based on the research result.